Non-Tariff Barriers and Trade Liberalization - Simon P. Anderson; Nicolas Schmitt (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper shows that governments have no incentive to introduce non-tariff barriers when they are free to set tariffs but they do when tariffs are determined cooperatively. We then show three results. First, with trade liberalization, there is a progression from u sing tariffs only to quotas, and to antidumping constraints (when quotas are jointly eliminated). Second, there is a narrowing of the range of industries in which each instrument is used. Third, the degree of tariff liberalization and of replacement of ta riffs by NTBs depend on industry characteristics. These results are roughly in line with the empirical evidence.
Keywords: 330; Tariffs; trade policy; reciprocal dumping; quotas; antidumping